Preeclampsia before fetal viability in women with primary antiphospholipid syndrome- materno-fetal outcomes in a series of 7 cases. (April 2020) - Mayer-Pickel, Karoline; Stern, Christina; Cervar-Zivkovic, Mila; Schöll, Wolfgang; Moertl, Manfred
Highlights: Women with APS are at increased risk for the development of preeclampsia, sometimes before fetal viability. Preeclampsia is associated with serious and especially long-term maternal and neonatal complications. Prevention of preterm delivery in pregnancies with preeclampsia should be attempted. Several management options for prolongation of pregnancy should be discussed with the patients. Abstract: Introduction: Preeclampsia complicates about 10–17 % of pregnancies with antiphospholipid syndrome (APS). It is often severe and might occur sometimes at early gestation. The development of preeclampsia before fetal viability is a huge challenge for obstetricians and demands an intensive discussion regarding the therapeutical options. Patients and methods: We retrospectively reviewed the data of 7 women with primary APS who developed preeclampsia before 24 weeks of gestation. Plasma exchange had been performed in four of the cases and two women received corticosteroids. One of the women had received 20 mg of pravastatin daily, starting at 18 weeks of gestation. Neonatal outcome was: live birth in four cases and IUFD in three cases. The main pediatric complications were noted in a 28-week-old premature born boy, who developed severe IRDS and thrombocytopenia. At the present time, the boy continues to have a retarded status. Discussion: This retrospective analysis revealed that women with APS can develop severe preeclampsia even before 20 weeks of gestation. Several management options for prolongation of pregnancy such as plasma exchange, pravastatin, LMHW, hydroxychloroquine/HCQ, or TNF-alpha blocker should be discussed with the patients. Optimal management of preeclampsia before 24 weeks of gestation usually depends on weighing the maternal and fetal complications from expectant management with prolongation of pregnancy versus the predominant fetal and neonatal risks of extreme prematurity from "aggressive" management with immediate delivery.